Development and Preliminary Evaluation of an Ice-Breaking-Integrated Archival Management Module in Two Vocational High Schools - Yanti Malasari; Hendra Jaya; Anas Arfandi (Sakura Digital Nusantara, 2026)
Purpose This study developed and evaluated an ice-breaking-integrated instructional module for Office Management, specifically within the Archival Management component in vocational high schools. The module was designed as an interactive learning resource to strengthen students’ learning motivation and improve their academic achievement. Methods This research employed a Research and Development (R&D) approach using the ADDIE model. The participants were 58 Grade XI Office Management and Business Services students from two public vocational high schools in Mamuju. Data were collected through classroom observations, interviews, expert validation, questionnaires, and pre- and post-tests. The data were then analyzed using descriptive techniques, paired-samples t-test, and N-Gain analysis. Findings The results indicated that the ice-breaking-integrated instructional module achieved a validity score of 97.0%, placing it in the highly valid category. The module was also considered highly practical based on teacher and student responses. In terms of effectiveness, its implementation enhanced students’ learning motivation and academic achievement, as reflected in a mastery learning rate of 96.55%, an increase in the mean score from 52.48 to 87.17, and an N-Gain score of 0.73, which falls within the high category. Research Implications These findings indicate that the ice-breaking-integrated instructional module provides an innovative alternative for Archival Management learning by promoting active, interactive, and student-centered engagement. Originality This study offers novelty by systematically integrating ice-breaking activities into an Archival Management module, providing an innovative vocational learning resource that enhances students’ motivation, participation, and learning outcomes.